Heredity of head dimensions and of cephalic index in man - Szopa, Jan (Anthropological Review, 1977)
The author’s aim was to investigate mode of inheritance of human head length and head breadth together with the resultant cephalic index. The material comprises 200 families inhabiting Nowy Sącz voivodeship. Total number of examined individuals (in the age of 3-87 years) amounts to 912. The method employed was that of computing moment-product correlation coefficients for all combinations of kins. Statistical significance of the results was checked by means of Student’s t-test. In the computations of parent-offspring correlations only the data for one, randomly selected, child from each family were included. Also heritability of investigated characters was considered. The results obtained (r values ranging from 0.17 to 0.58) enable one to conclude that head length and head breadth are determined polygenicaly, i.e. by a number of alleles at various loci acting cumulatively and without dominance of any head dimension. Heritability of head length and head breadth is shown to be similar — 0.51 to 0.76 depending on the way of estimation. Heritability of the cephalic index is much lower (0.34 - 0.58). The phenomenon of “maternal regulator” is distinct in considerably higher correlation coefficients for mother-offspring and sibling-sibling combinations than those for father-offspring combinations. Absolute dimensions investigated show certain relation to chromosome X — either by direct localisation in it of some alleles determining the dimensions or, what seems more probable, by indirect pleiotropic action of alleles localised in the chromosome X on various metrical characters. Within-family similarities of the cephalic index (smaller than those of absolute dimensions) perhaps result from effects of separate idependent polygenic inheritance of head dimensions, but not from action of specific alleles. This points towards limited usefulness of the cephalic index in studies carried on families.